Reading Spatial Governmentality, Understanding Mentality of Violence in Lampuki, Puya ke Puya, and Dawuk - Harfiyah Widiawati; Melani Budianta; Manneke Budiman (Universitas Airlangga, 2022)
Post-Reform Indonesian novels such as Lampuki by Arafat Nur, Dari Puya ke Puya by Faisal Oddang, and Dawuk by Mahfud Ikhwan critically question the problem of governmentality, inviting us to ponder upon how works of literature formulate a social change in terms of state crisis, economic uncertainty, and other instabilities. The theme of spatial governmentality in the form of conflicts due to land appropriation/acquisition and land use, shows the dynamic of power, spread to various state and non-state actors with diverse interests. This paper analyzes how spatial governmentality embodies itself in the narrative structure of the three novels in order to eventually scrutinize how power implicates structural violence. The discourse on governmentality frequently uses benign jargon such as progress, development, modernity; while in fact it is a process full of structural violence, often involving the deprivation of marginalized people’s land and livelihood. The change in spatial form, followed by economic and social transformation, enables those in power to dominate the circle of production and deprive the right to live through the limitation/closing of access to modality, i.e. the land as source of livelihood.